POST GRADUATE STUDENTS’ PERCEPTION OF EDUCATIONAL ENVIRONMENT AT ARMY MEDICAL COLLEGE, RAWALPINDI: ASSESSMENT BY PHEEM ( POST GRADUATE EDUCATION ENVIRONMENT MEASURE): PG Students’ Perception- Educational Environment - Hashim, Rizwan; Qamar, Khadija; -Zuhra, Fatima- tuz; Ali, Salman (Pakistan Armed Forces Medical Journal, 2015)
Original Article Objectives: To assess the post graduate students’ perception of various aspects of the learning and educational environment at Army Medical College, Rawalpindi. Study Design: A descriptive study. Place and Duration of Study: Army Medical College, Rawalpindi from May 2014-July 2014. Participants and Methods: The modified Postgraduate Hospital Educational Environment Measure (PHEEM) a scored 34 item questionnaire was administered to evaluate various aspects of the learning environment. Three domains of the learning environment were covered with the help of PHEEM scores: perceptions of autonomy; perceptions of teaching; and perceptions of social support. Total and subscale scores were calculated according to Likert scale. Descriptive statistics were used to calculate mean SD. Analysis of variance (ANOVA) was used to compare scores between different departments. Results: Total 39 postgraduate trainees were included in the study. Average of total score came out to be 107, whereas for perception of teaching it was 45.57 (SD = 5.22, range: 43 – 48), for social support it was 24.76 (SD = 3.76, range: 21 – 27) and for perception of autonomy it was 36.84 (SD = 4.09, range: 33 - 39). The overall and subscale scores were also compared between post graduates of the different departments of the public sector medical colleges. The education climate was rated as more positive than negative determined by overall PHEEM scores. Conclusion: Army Medical College as an institution has a positive education environment.